PENGARUH LAYANAN KONSELING INDIVIDUAL TERHADAP PEMBENTUKAN PERILAKU JUJUR PADA SISWA KELAS VIII DI SMP NEGERI 6 BUKITTINGGI - Kurniadi Fara Mulya; Budi Santosa; Alfi Rahmi; Syawaluddin (STKIP Subang, 2024)
Honesty is an innate disposition that is crucial to practise in our daily lives. Nevertheless, there are individuals who exhibit dishonest behaviour, as evidenced by the occurrence among students at SMP N 6 Bukittinggi. This behaviour is characterised by various symptoms, including students disregarding exam rules by seeking answers from their peers, making incorrect payments for snacks in the canteen, falsely excusing themselves to the teacher to go to the toilet while their snacks are actually in the school canteen, and so forth. This study falls under the category of Pre-Experimental Design research, specifically the One Group Pretest and Posttest Design model, which does not include a comparison group or randomisation. The research focused on individuals in the eighth grade. The study sample included 10 individuals selected by purposive sampling approach. Data was gathered with an instrument equipped with a Likert scale to assess the level of honesty shown by pupils. This study seeks to examine the impact of the administered therapy on the dependent variable. The data analysis methodology employs the method of hypothesis testing, specifically the Wilcoxon signed ranks test. The statistical test results obtained from the sig (2-tailed) value are 0.005, which is less than the alpha level of 0.05. Therefore, we can conclude that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This implies that individual counselling services have a significant impact on the development of honest behaviour among students at SMP Negeri 6 Bukittinggi.